2013
DOI: 10.1074/jbc.m113.468892
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Mycobacterium tuberculosis Polyketide Synthase 11 (PKS11) Reveals Intermediates in the Synthesis of Methyl-branched Alkylpyrones

Abstract: Background: Polyketide synthases (PKSs) synthesize complex lipid components of the cell wall in M. tuberculosis. Results: We determined the crystal structure of M. tuberculosis PKS11 and identified its substrate, intermediates, and product. Conclusion: M. tuberculosis PKS11 synthesizes a unique cyclic methyl-branched alkylpyrone. Significance: Our identification of alkylpyrones as the product of this PKS suggests a previously unknown component of the mycobacterial cell wall.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 40 publications
0
29
0
Order By: Relevance
“…This is analogous to PKSA and PpASCL, whereby a replacement of bulky Thr197 in alfalfa CHS with a smaller Gly205 in PKSA and Gly225 in PpASCL is believed to widen the entrance of the acyl-binding tunnel, enabling them to utilize larger acyl-CoAs as starters [63]. The crystal structure of PKS11 was recently solved (PDB ID: 4JAP), and a buried hydrophobic tunnel was also revealed, together with a CoA-binding tunnel [73]. Co-crystallizations and in vitro enzyme assays revealed that PKS11 can catalyze the decarboxylative condensation of methylmalonyl-CoA with palmitoyl-CoA (C16) or stearoyl-CoA (C18), followed by another decarboxylative condensation of malonyl-CoA and lactonization to generate methylated alkylpyrones.…”
Section: Biosynthesis Of Alkylpyrones By Pks11 and Pks18mentioning
confidence: 95%
See 2 more Smart Citations
“…This is analogous to PKSA and PpASCL, whereby a replacement of bulky Thr197 in alfalfa CHS with a smaller Gly205 in PKSA and Gly225 in PpASCL is believed to widen the entrance of the acyl-binding tunnel, enabling them to utilize larger acyl-CoAs as starters [63]. The crystal structure of PKS11 was recently solved (PDB ID: 4JAP), and a buried hydrophobic tunnel was also revealed, together with a CoA-binding tunnel [73]. Co-crystallizations and in vitro enzyme assays revealed that PKS11 can catalyze the decarboxylative condensation of methylmalonyl-CoA with palmitoyl-CoA (C16) or stearoyl-CoA (C18), followed by another decarboxylative condensation of malonyl-CoA and lactonization to generate methylated alkylpyrones.…”
Section: Biosynthesis Of Alkylpyrones By Pks11 and Pks18mentioning
confidence: 95%
“…The ability of PKS11 to select different extenders at different stages of polyketide elongation is intriguing, and more structural studies in this aspect will be useful for the generation of clinically important unnatural polyketides. The crystal structure of PKS11 was recently solved (PDB ID: 4JAP), and a buried hydrophobic tunnel was also revealed, together with a CoA-binding tunnel [73]. Co-crystallizations and in vitro enzyme assays revealed that PKS11 can catalyze the decarboxylative condensation of methylmalonyl-CoA with palmitoyl-CoA (C16) or stearoyl-CoA (C18), followed by another decarboxylative condensation of malonyl-CoA and lactonization to generate methylated alkylpyrones.…”
Section: Biosynthesis Of Alkylpyrones By Pks11 and Pks18mentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent KS crystal structures provide the first views of bona fide substrates as covalent intermediates in the KS active site. One structure is for a PKS that acts on acyl-CoA substrates [54], and the other is excised from a trans -AT pathway [51]. The spacious KS active sites appear to provide binding pockets adapted to their substrates, and based on these high-resolution substrate complexes, it is challenging to predict the position of a new building block delivered through the entrance for the module ACP.…”
Section: Overall Architecturementioning
confidence: 99%
“…M. smegmatis, a fast-growing saprophytic relative of Mtb, is a potential expression host for Mtb genes overcoming many of the restrictions of E. coli (36)(37)(38)(39). Unexpectedly, however, only nine proteins of H37Rv represented by 27 structures were produced in M. smegmatis (37,(40)(41)(42)(43)(44)(45)(46). Clearly the faster growth and production rates of E. coli ensure that it remains the most popular expression host.…”
Section: Technical Aspects Of Mtb Structural Analysismentioning
confidence: 99%